2011
DOI: 10.1530/eje-10-1080
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of a missense mutation in resistin in two patients with severe obesity and insulin resistance

Abstract: Objective: In this study, we hypothesized that mutations in the resistin encoding gene, RETN, may cause a monogenic form of obesity. Design/methods: We screened the coding region of RETN in 81 morbidly obese adults, 263 overweight and obese children/adolescents, and 116 healthy lean subjects. In vitro experiments include qPCR, ELISA, and western blot for WT and mutant resistin transfected into 3T3-L1 adipocytes. Results: Mutation analysis identified five sequence variants in our patient populations:0 -UTR C100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…A recent publication described a heterozygous C78S missense mutation in RETN in an obese patient [Beckers et al, ]. The mutation was inherited from one of the two obese parents.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication described a heterozygous C78S missense mutation in RETN in an obese patient [Beckers et al, ]. The mutation was inherited from one of the two obese parents.…”
Section: Discussionmentioning
confidence: 99%
“…Beckers et al identified the first missense mutation C78S in resistin in a morbidly obese proband and his obese mother. This finding encourages the study of variants in the RETN gene coding region to elucidate their involvement in pathogenesis [18]. It was estimated that genetic factors can explain up to 70% of the variation in circulating resistin levels [19].…”
Section: Introductionmentioning
confidence: 96%